A comparison study of three heating assisted enzyme inactivation pretreatments on the physicochemical properties and edible quality of highland barley grain and flour. (March 2022) - Li, Meng-jia; Wang, Hao-ran; Tong, Li-Tao; Fan, Bei; Yang, Xi-juan; Sun, Ruo-qi; Liu, Li-ya; Wang, Feng-zhong; Wang, Li-li
Abstract: Enzyme inactivation is vital to improve the shelf life of highland barley (HB), but the impacts of different heating assisted enzyme inactivation pretreatment (HAEIP) on structure, physicochemical properties and edible quality remain unclear. This study evaluated the effects of three representative HAEIP for microwave, roasting and superheated steam (SS) on the properties of HB grain and flour based on the 50% or 60% inactivation rates for lipase and complete inactivation for peroxidase. Results showed that microwave and SS treatments had the highest and lowest cracking ratio respectively. For the HB edible qualities, the shorter cooking times were observed in R-60 (26 ± 0.84), SS-50 (27 ± 0.09) and SS-60 (27 ± 0.07) groups. Meanwhile, the hardness and chewiness of roasted HB were significantly higher than that in microwaves and SS groups. The HB flour properties varied with different HAEIP. Although all pretreatments showed a substantial reduction in the flour viscosities with treatments intensity increased, the PV values in the two SS groups were the highest. The microwave treatment had the biggest impact on the relative crystallinity and gelatinization degree, while SS pretreatment had the best performance and could be an effective, practical enzyme inactivation methods and enhance HB product quality. Graphical abstract: Image 1 Highlights: The highland barley grain and flour qualities varied with different heat treatments. Roasting treatment had a negative effect on the texture quality of cooked samples. Microwave group had the highest gelatinization degree and lowest crystallinity. Superheated steam treatment caused the least change in starch pasting properties.